Synthesis and Characterization of All-Acrylic Tetrablock Copolymer Nanoparticles Waterborne Thermoplastic Elastomers via One-Pot RAFT Aqueous Emulsion Polymerization - Deane, Oliver J (Chemistry of materials : a publication of the American Chemical Society, 2024)
© 2024 The Authors. Published by American Chemical Society.